Rys historyczny prawnych aspektów ochrony weterynaryjnej zwierząt w Polsce - Listos, Piotr; Gryzińska, Magdalena; Dylewska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Treatment of animals by aman as asphere that requires legislation began to take place in modern history at the beginning of the nineteenth century. Objectives and content of legislation on animal protection, developed according to the needs of man, has been changing in different historical epochs. One of the main trends of animal protection outlined by law is their veterinary protection. It is amultidimensional form of legal protection of animals and it incorporates in each different kind of animal protection, in Poland delineated by the legislature.The first regulations on the veterinary protection were formed in Poland along with the development of local law that was established on the principles of the municipal law of Magdeburg. These regulations have evolved over the years, until modern times.The fact of major importance for the veterinary protection was Polish accession to the European Union. It resulted in the need for implementation of anumber of European regulations into national law. Analysis of regulations of veterinary protection in Poland leads to the conclusion that the fight against infectious diseases occurring among animals was the main form of protection. An example of the impact and effectiveness of the established regulations is combating one of the most dangerous zoonotic diseases — rabies.
Keywords: ochrona zwierząt; ochrona weterynaryjna; Polska